Strategies for realizing equitable education rights for people with disabilities at Nurul Maksum Inclusive Islamic Boarding School Semarang - Lestari, Eta Yuni; Ani Purwanti; Ratna Herawati (Universitas Negeri Yogyakarta, 2025)
The problems experienced by vulnerable groups, especially people with disabilities, pose a challenge to conducting in-depth studies to produce innovative solutions. This article examines the inclusive education model as a strategy for fulfilling the educational rights of people with disabilities implemented in Islamic boarding schools. This article aims to determine how inclusive education is implemented in Islamic boarding schools, what strategies are used, and the implications of inclusive education in Islamic boarding schools. The research method used is qualitative research using secondary data sources, such as the primary data obtained from interviews with the caretaker of the Nurul Maksum inclusive Islamic boarding school on the YouTube channel: Sahabat Santri Mengabdi. The second secondary data source comes from journal articles and books relevant to the research theme. The results of the study show that the inclusive education model implemented in Islamic boarding schools uses an Islamic approach with an emphasis on patience, sincerity, and Lillahitaala. The implementation of inclusive education prioritises the needs of students with disabilities, especially in learning to read and memorise the Quran. This study contributes to the development of fulfilling the right to education for people with disabilities, which can be implemented in Islamic boarding schools using special methods.